A new combination and an updated identification key for Rhabdocaulon and the differences from Hoehnea (Lamiaceae, Nepetoideae, Mentheae, Menthinae) - Bräuchler, Christian (Phytotaxa, 2020)
A new combination for the recently described Hoehnea grandiflora Funez & Hassemer (2018: 160) is porposed in Rhabdocaulon (Bentham, 1834: 411) Epling (1936: 134). Characters distinguishing Rhabdocaulon and Hoehnea Epling in Epling & Stewart (1939: 8)  are outlined and an updated identification key is provided for Rhabdocaulon.